1966
DOI: 10.1002/ar.1091550406
|View full text |Cite
|
Sign up to set email alerts
|

The number of nerve fibers in the limb of the mouse and its relation to regenerative capacity

Abstract: In regeneration of the salamander limb the nerve must satisfy a quantitative threshold below which regeneration does not occur. The present work explores the reason for the inability of the mammalian limb to regenerate by analyzing the number of nerve fibers available in the wound of the amputated limb. The number expressed per unit area of amputation wound is only 16% of that of the newt, Triturus, a regenerating form. It is known that when the number of fibers in the newt's limb is reduced to about a third o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The greater the number or caliber of nerves per unit amputation area, the larger the amount of trophic agent delivered. He and Rzehek found, for instance (15), that in the mammal (mouse) the limb contains only 16% of the number of nerves per unit area of amputated limb as that found in the newt. These nerves are also thinner.…”
Section: Discussionmentioning
confidence: 97%
“…The greater the number or caliber of nerves per unit amputation area, the larger the amount of trophic agent delivered. He and Rzehek found, for instance (15), that in the mammal (mouse) the limb contains only 16% of the number of nerves per unit area of amputated limb as that found in the newt. These nerves are also thinner.…”
Section: Discussionmentioning
confidence: 97%
“…Calculation of the number of nerve fibers per unit area in this lizard gave a value that was about half that obtained for the salamander (Zika and Singer, 1965). Equivalent calculations for mammalian limbs indicated that the corresponding value here was half again that of the lizard (Rzehak and Singer, 1966). T h e implication seems to be that there is a relationship between the degree of peripheral innervation and the ability to regenerate.…”
Section: Nerves and Neural Factorsmentioning
confidence: 62%
“…The threshold was calculated to be about one third to one half the normal nerve supply. It has been shown by Rzehak and Singer [1966] that the mouse, which does not regenerate amputated limbs, has only 16% as many nerve fibers per unit area as the regenerating urodele. The nerve deficit in limbs is smaller in the lizard, a form that can be stimulated to regenerate by deviating additional nerves from the opposite limb to the amputated side [Singer, 1961;Kudokotsev, 19621.…”
Section: Introductionmentioning
confidence: 99%